UMPSA honours former Vice Chancellor and Deputy Vice Chancellor Research and Innovation for their contributions to university - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
PUTRAJAYA, 25 January 2025 – The Majlis Sanjungan Budi was held to honour the former Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato’ Ts. Dr. Yuserrie Zainuddin, and the former Deputy Vice-Chancellor (Research and Innovation), Professor Ts. Dr. Kamal Zuhairi Zamli, in recognition of their dedicated service and significant contributions to the university.